The national question in the Russian Duma. Speeches by Milyukoff [Miljukov], Tchkeidze [Ccheidze], Kerensky [Kerenskij] i dr. Transl. and arranged by E.L. Minsky [Minskij] (London, 1915)
Publ. by the Jewish Labour League.